High level Mammalian taxonomy: a response to Hedges (2011) - Asher, Robert J.; Helgen, Kristofer M. (Zootaxa, 2011)
Hedges (2011) recently published a critique of our 2010 BMC Evolutionary Biology article (Asher and Helgen 2010) in which he expressed a preference for the name Afrosoricida Stanhope et al. 1998 to signify the mammalian clade of tenrecs (Tenrecidae) and golden moles (Chrysochloridae). He disagreed with what he claimed to be our rationale for preferring another name for this group, Tenrecoidea McDowell 1958. Here is his portrayal of our taxonomic philosophy: "[Asher & Helgen] suggested that strict priority be used as a criterion for high-level names and that such priority be based on group content rather than the procedure used for low-level taxa, anchored to constituent taxa. ... [They] have proposed a radical departure from convention" (Hedges 2011:67–68).